KAJIAN KEBIJAKAN PENGUASAAN LAHAN DALAM KAWASAN KESATUAN PENGELOLAAN HUTAN (KPH) DI KABUPATEN LAMPUNG SELATAN - Sylviani Sylviani; Haryatno Dwiprabowo; Elvida Yosefi Suryandari (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
Forest management could not be separated from problems or land conflicts. Factors affecting land conflicts are economic, social, ecological and different agricultural needs. Several forms of land conflicts are overlapping land use and land ownership conflict. Social conflicts may occur between the settlers and the natives. These all are the obstacles in the development of Forest Management Unit (FMU). This study aimed to identify the parties and land claims in the form of land management, identify institutional and tenure rules in the FMU and policy recommendations. The study was conducted by the method of Rapid Land Tenure Assessment (RATA), to assess, analyze, understand, and describe briefly the problem and/or conflict of complex land tenure system. The result showed that the problem of tenure in the FMU in South Lampung Regency happened because forest area have been occupied by residential, public/social and modern market in the definitive village. The role of the parties/actors in land tenure in the FMU is crucial. The central government issued the policy but did not do evaluation, especially the area boundaries and inactive permits. While the local government issued a regulation of definitive village formation and publishes an annual tax return for the land which is then use as legal tenant claims. In institutions, there is no coordination between the Ministry of Forestry (the ruler's) with stakeholders in local government in the issuance of land certificates. Suggested policies are to accommodate the needs of local communities. One approach that can be taken by the Ministry of Forestry is by making the cultivated forest land to become the HTR program, HKm or Village Forest and resetting forest area boundaries.